1981
DOI: 10.1002/cber.19811140125
|View full text |Cite
|
Sign up to set email alerts
|

Ein Verfahren zur Synthese von α‐Glycosiden der 3‐Amino‐2,3,6‐tridesoxyhexopyranosen aus Glycalen

Abstract: Das Anomerengemisch der Hex-2-enopyranosylazide 2 und 3, die jeweils mit den 3-Azidoglycalen 5 bzw. 6 im Gleichgewicht stehen, wird mit Cyclohexanol und N-Iodsuccinimid zu den 3-Azido-2-iod-Derivaten mit a-D-oltro-(4) und a-D-manno-Konfiguration (9) umgesetzt. Deren reduktive Aufarbeitung nebst Acetylierung ermdglicht die Synthese von 3-Acerylamino-2,3-didesoxy-aglycosiden der D-ribo-(7) und der D-arabino-Struktur (8). In einer vergleichbaren Reaktionssequenz wird aus Di-0-acetyl-L-rhamnal(10) in nur drei Stuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The D isomer 5 has also been prepared from carbohydrate precursors and has been a byproduct in syntheses of D-daunosamine (2) 26,27,33 (43) as a route for generating pyranose intermediates with a nitrogenous functionality at C-3. In the sequence employed by Heyns et al 129,130 and shown in Scheme XXIII, the diacetate derivative 138a of rhamnal ( 43) was reacted with sodium azide and boron trifluoride in ether. 132 The generated mixture of the C-l (139a and 140a) and C-3 (141a and 142a) azide epimers was shown to be in equilibrium through [3,3]-sigmatropic rearrangement.…”
Section: Racemic Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The D isomer 5 has also been prepared from carbohydrate precursors and has been a byproduct in syntheses of D-daunosamine (2) 26,27,33 (43) as a route for generating pyranose intermediates with a nitrogenous functionality at C-3. In the sequence employed by Heyns et al 129,130 and shown in Scheme XXIII, the diacetate derivative 138a of rhamnal ( 43) was reacted with sodium azide and boron trifluoride in ether. 132 The generated mixture of the C-l (139a and 140a) and C-3 (141a and 142a) azide epimers was shown to be in equilibrium through [3,3]-sigmatropic rearrangement.…”
Section: Racemic Synthesesmentioning
confidence: 99%
“…Using a sequence similar to that shown in Scheme XXIII for the synthesis of L-acosamine,129, 130 Thiem and Springer261 reported preparations of ristosamine and 3-epi-daunosamine from L-rhamnal. The 4-hydroxyl group in the isomeric iodo azide intermediates (143 and 144) was oxidized to give azido enosidulose isomers which were converted to L-ristosamine and L-3-epidaunosamine.…”
Section: Addendummentioning
confidence: 99%